Vaccination for SARS-CoV-2 in Patients With Psoriatic Arthritis: Can Therapy Affect the Immunological Response? - Benucci, Maurizio; Damiani, Arianna; Infantino, Maria; Manfredi, Mariangela; Lari, Barbara; Grossi, Valentina; Mariotti, Elena Biancamaria; Corrà, Alberto; Aimo, Cristina; Quintarelli, Lavinia; Verdelli, Alice; Li Gobbi, Francesca; et al. (Frontiers in Medicine, 2022)
Background. A few studies on vaccination in patients with rheumatic diseases, including arthritis, connective tissue diseases, vasculitis and psoriatic arthropathy (PsA), demonstrated reduced production of neutralizing antibodies to SARS-CoV-2 Spike RBD (receptor-binding domain contained in the N-terminal of the S1 globular head region) when compared to the general population. Objective. The aim of our study was to observe whether different therapies for PsA [methotrexate, anti-TNF antibodies, soluble TNF receptor (etanercept) or IL-17 inhibitors] have a different impact on SARS-CoV-2 vaccination in a homogeneous population of patients. Methods. We enrolled 110 PsA patients in remission, assessed with Disease Activity in PSoriatic Arthritis (DAPSA). Of these: 63 were in treatment with anti-TNF alpha therapy (26 etanercept, 15 certolizumab, 5 golimumab, 17 adalimumab); 37 with anti-IL17 secukinumab; 10 with methotrexate. All patients underwent vaccination for SARS-CoV-2 with mRNA BNT162b2 vaccine. Assessment of absolute and percentage lymphocyte subsets and anti-SARS-CoV-2 Spike RBD IgG antibody value three weeks after the second vaccine dose were performed. In addition, the serum antibody levels of 96 healthy healthcare workers (HCW) were analyzed. Results. Mean disease activity calculated with DAPSA was 2.96 (SD 0.60) and it did not differ between patients taking different medications (p 0.779). Median levels of neutralizing antibodies to SARS-CoV-2 Spike RBD were 928.00 binding antibody unit (BAU)/mL [IQR 329.25, 1632.0]; 1068.00 BAU/mL [IQR 475.00, 1632.00] in patients taking MTX, 846.00 BAU/mL [IQR 125.00, 1632.00] in patients taking etanercept, 908.00 BAU/mL [IQR 396.00, 1632.00] in patients taking anti-IL17 and 1148.00 BAU/mL [IQR 327.00, 1632.00] in patients taking TNF-alpha inhibitors, without statistically significant differences between these groups. Mean serum antibody level of HCW group was 1562.00 BAU/mL [IQR 975.00, 1632.00], being significantly higher than in the patient group (p = 0.000816). Absolute and percentage count of lymphocyte subsets were not statistically different between the subgroups under different treatments and when compared with HCW. Conclusions. As for other rheumatic diseases on immunomodulatory treatment, our data showed a reduced humoral response in PsA patients compared to the control group. However, antibody response did not significantly differ between groups treated with different medications.